Peran Orang Tua Dalam Mengembangkan Minat dan Bakat Anak Usia Dini - Mutingah, Mutingah; Ali, Musyafa; Prawening, Cesilia (Paedagogie, 2026)
Parents' busyness often leads to a lack of attention to the development of children's interests and talents, even though these two aspects are the main foundation in optimizing one's potential from an early age. This study aims to describe the role of parents in developing children's interests and talents and analyze the impact of these involvements. The method used is a qualitative approach with a case study type located at Diponegoro Kindergarten 101 Pejogol. Data collection was carried out through observation techniques, in-depth interviews, and documentation, while data analysis used data reduction, data presentation, and conclusion drawing techniques. The results of the study show that the role of parents as educators, guides, motivators, and facilitators contributes positively to increasing children's confidence, motivation, and creativity. Parental support through the provision of consistent facilities and assistance has also been proven to be able to optimize children's potential and strengthen the emotional bond between parents and children. In conclusion, the active involvement of parents is a key factor in the development of interests and talents, so continuous synergy between schools and parents is needed to support children's overall growth and development.